2018
DOI: 10.1093/gbe/evy165
|View full text |Cite
|
Sign up to set email alerts
|

Whole Genome Incorporation and Epigenetic Stability in a Newly Synthetic Allopolyploid of Gynogenetic Gibel Carp

Abstract: Allopolyploidization plays an important role in speciation, and some natural or synthetic allopolyploid fishes have been extensively applied to aquaculture. Although genetic and epigenetic inheritance and variation associated with plant allopolyploids have been well documented, the relative research in allopolyploid animals is scarce. In this study, the genome constitution and DNA methylation inheritance in a newly synthetic allopolyploid of gynogenetic gibel carp were analyzed. The incorporation of a whole ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 112 publications
(137 reference statements)
0
15
0
1
Order By: Relevance
“…Polyploids are very rare but have been reported in vertebrates including fish, amphibians and reptiles. Unisexual reproduction, such as parthenogenesis, gynogenesis and hybridogenesis, are often associated with polyploids, because the alternative unisexual reproduction can help polyploids to pass through meiosis barrier and reproduction bottleneck after polyploidy (Vandepoele et al, 2004;Gui and Zhou, 2010;Choleva and Janko, 2013;Avise, 2015;Zhou and Gui, 2017;Shao et al, 2018;Chen et al, 2020). However, the direct consequences of polyploidy on sex determination system and reproduction mode transition remain unknown in natural polyploids as it is very difficult to return to the past polyploidy events.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Polyploids are very rare but have been reported in vertebrates including fish, amphibians and reptiles. Unisexual reproduction, such as parthenogenesis, gynogenesis and hybridogenesis, are often associated with polyploids, because the alternative unisexual reproduction can help polyploids to pass through meiosis barrier and reproduction bottleneck after polyploidy (Vandepoele et al, 2004;Gui and Zhou, 2010;Choleva and Janko, 2013;Avise, 2015;Zhou and Gui, 2017;Shao et al, 2018;Chen et al, 2020). However, the direct consequences of polyploidy on sex determination system and reproduction mode transition remain unknown in natural polyploids as it is very difficult to return to the past polyploidy events.…”
Section: Discussionmentioning
confidence: 99%
“…Significantly, two rounds of polyploidy events have been revealed to occur in the polyploid complex of Carassius, in which an earlier allopolyploidy at about 18.5 million years ago (Mya) has led to ancestral allotetraploid C. auratus with 100 chromosomes, and a recurrent autotriploidy at about 0.5 Mya has produced the extant hexaploid C. gibelio with about 150 chromosomes (Li et al, 2014). The tetraploid C. auratus have returned to normal diploid status that can reproduce by sexual reproduction, whereas hexaploid C. gibelio has also evolved to reproduce successfully via unisexual gynogenesis (Gui and Zhou, 2010;Li and Gui, 2018). In this study, we synthesized a group of artificial octoploids by incorporating one genome (50 chromosomes) of tetraploid C. auratus with sexual reproduction ability into the unisexual gynogenetic hexaploid C. gibelio, and found that the X/Y sex determination system from tetraploid C. auratus has been transferred into the synthetic octoploids.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…随着对银鲫独特的多重生殖方式 [69,70] 以及其六倍体遗传背景对其他鱼类精子染色体组或染 色体片段的包容性和整合性的认识 [71] , 银鲫新品种纷 至沓来. 2008年, 本研究组 [44] 通过对不同克隆系交配 的子代应用分子标记辅助育种技术培育出核质杂种异 育银鲫"中科3号"; 2015年, 与中国水产科学研究院长 江水产研究所合作, 参与培育出融入有鲤精子全部染 色体的"长丰鲫" [72,73] ; 2018年, 基于基因组reads测序 深度比较策略和分子模块筛选鉴定, 培育出异育银鲫 "中科5号" [45,46] . 在人工雌核生殖技术方面, 1986年, 吴 清江等人 [74] 应用该技术结合性反转, 培育出可规模化 养殖的全雌鲤.…”
Section: 他品种在其培育过程中也应用了杂交育种技术 20世unclassified